THE ADAPTATION STUDY OF SCHOOL READINESS EVALUATION TEST TO TURKISH - Pınar BAĞÇELİ KAHRAMAN (Fırat University, 2019)
The purpose of the present study was to adapt the “Brainline School Readiness Test”. For the validity and reliability analyses, the test was performed to 30 7 year old students in the primary school. In the process of adaptation, translation to Turkish was done by two experts and then the test was translated back to English. It was found that there was unity between the expressions of the original form and the form translated from Turkish to English. The Turkish form was examined in terms of clarity of expressions and the form was finalized after making the necessary corrections. The realibility was analysed by using Kuder Richardson 20 coefficient and the test-retest correlation. The validity of the test was analysed by the means criteria validity which was based on teacher assessment and the development forms of children in preschool. The significance of the correlation between avarage scores of teacher assessments and avarage scores of development forms obtained from School Readiness Evaluation Test, was tested by means of Pearson’s Momentus Multiplication Correlation technique. It was determined that the realibility coefficient of this test was found to be .89.4. With the aim of determining whether the test provided consistent measurements depend on time or not, the test was perfomed a second time after two weeks to the children. The test-retest correlation was calculated by using Pearson Correlational coefficient and was found to be .94. It was found that this test is a valid and reliable instrument. It can be recommended that a wider sampling can be involved in the study.